The impact of interprofessional collaboration on EPS counselors’ job satisfaction - Hallaråker, Helene; Hesjedal, Elisabeth; Olsen, Kathrin; Tveitnes, Marianne S.; Herlofsen, Camilla; Cameron, David L.; Brandmo, Christian (Frontiers in Education, 2025)
Educational Psychological Services (EPS) counselors play an essential role in supporting students with special educational needs through assessments, interventions, and collaboration with key stakeholders. This study examines the relationship between interprofessional collaboration, job satisfaction, and intention to leave among EPS counselors, including the variables knowledge about collaboration, trust, affective commitment, and time pressure. Based on a cross-sectional design with structural equation modeling, the study analyzes data from 637 EPS counselors concerning their interprofessional collaborative practices with kindergartens, schools, child welfare services, and health services. The findings highlight that knowledge about collaboration, trust, and sufficient time are essential for effective interprofessional collaboration with kindergartens and schools. Affective commitment was strongly associated with job satisfaction, while time pressure was closely linked to EPS counselors’ intention to leave. Although interprofessional collaboration was not strongly related to job satisfaction or intention to leave, negative collaboration experiences with kindergartens and schools were positively related to EPS counselors’ intentions to leave. These findings underscore the importance of ensuring that EPS counselors have the necessary knowledge, trust, and time for effective interprofessional collaboration.